DNA interstrand cross-linking agents and their chemotherapeutic potential - Brulíková, Lucie; Hlaváč, J; Hradil, P (Current medicinal chemistry, 2012)
DNA interstrand cross-linking (ICL) agents are an important group of cytotoxic drugs with the capability of binding covalently between two strands of DNA, thereby preventing vital processes such as replication or transcription in dividing cells. In anticancer therapy however, their potential is limited due to the resistance by various mechanisms. In order to develop highly effective antitumor drugs it is necessary to study both effective ICL formations and their subsequent repair mechanisms. This review presents an overview of development over the past decade and the use of both well-known and new DNA interstrand cross-linking agents. Their potential in applications especially as anticancer chemotherapeutics in the framework of current knowledge of repair mechanisms and development of combined chemotherapy is discussed.
Keywords: anthrachinony; oprava DNA; Azepines; aziridiny; mechlorethamin; Anthraquinones; Neoplasms; nádory; DNA; lidé; alkaloidy; azepiny; Antineoplastic Agents; protinádorové látky; komplexní sloučeniny; Mechlorethamine; DNA Repair; Cross-Linking Reagents; Coordination Complexes; reagencia zkříženě vázaná; Alkaloids; Aziridines; Humans